Assessment of Water Quality Using Macrobenthos as Bioindicator and Its Application on Abundance-Biomass Comparison (ABC) Curves - Suci Wulan Pawhestri; Jafron. W Hidayat; Sapto P Putro (International Journal of Science and Engineering, 2015)
Abstract -Activities of aquaculture and industry which is directly adjacent to an aquatic environment may potentially result in increasing organic matter and causes a decreasing quality of water in it. Macrobenthos can be used as an bioindicators to detect environmental disturbances occur in the aquatic environment. This study aims to determine the level of environmental disturbance in aquatic environments using macrobenthic assemblages and their application in the abundance and biomass curves and it was compared to the values of diversity and similarity indices. Locations of this study is polyculture ponds and coastal of PT. Kayu Lapis Indonesian located in Mororejo Village, Central Java. Based on the abundance of macrobenthos results shows that in coastal area of PT. Kayu Lapis Indonesia is dominated by Cirratulidae (60%) from Polychaeta while in polyculture ponds is dominated by Potamididae (58%). Based on the abundance and biomass comparison (ABC) curves, the polyculture ponds were categorized as undisturbed area, whereas the coastal area of PT. Kayu Lapis Indonesia was categorized as moderately polluted for the second sampling time. Whilst the values of diversity (H’) and similarity (e) indices indicated low for all stations, the ABC curve of macrobetnhic assemblages is effective to  demonstrate the level of environmental disturbance occurs in aquatic environments.